The development of the English novel - Dille, Grace (My University, 1897)
Introduction: One of the most interesting portions of the history of English literature is that which treats of the growth of the novel. We are accustomed to speak of that growth as a most rapid one, and, indeed, if we go back no farther than the time of Richardson to find the origin of the English novel, we cannot but admit that the rapidity of its development has been truly phenomenal. However, we should bear in mind the thought that for centuries the way had been preparing for this great work of fiction. Away back in Anglo-Saxon England, seated at the feast in long halls whose walls were hung with trophies of the chase and with armor which glittered and flashed in the firelight, stern-bearded warriors were wont to listen with delight to the long tales of the gleemen—tales of mighty heroes, of fierce battles, of superhuman deeds—chanted in monotonous tone to the accompaniment of the harp. Softer, smoother than these were the Norman minstrel songs which later came to replace them. Sung first at the court of William, they soon caught the English fancy and were echoed far and wide. Instinct as these later songs were with the spirit of chivalry and romance, they mark the dawn of the emotional element in story-telling. Still later came Geoffrey Chaucer, king of the story-tellers, in whose skillful hands the metrical romance reached its climax. Nor, was he master of verse alone. His characters were real men and women, such as had never before been painted, such as were not again painted until the days of Shakespeare.
Citation: Dille, Grace. The development of the English novel. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Literature; History; Novel; Storytelling; Theses; Manuscripts (documents)